Proceedings of the 19th ACM International Conference on Multimodal Interaction 2017
DOI: 10.1145/3136755.3136817
|View full text |Cite
|
Sign up to set email alerts
|

Data augmentation of wearable sensor data for parkinson’s disease monitoring using convolutional neural networks

Abstract: While convolutional neural networks (CNNs) have been successfully applied to many challenging classification applications, they typically require large datasets for training. When the availability of labeled data is limited, data augmentation is a critical preprocessing step for CNNs. However, data augmentation for wearable sensor data has not been deeply investigated yet.In this paper, various data augmentation methods for wearable sensor data are proposed. The proposed methods and CNNs are applied to the cla… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
366
0
2

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
4
2

Relationship

0
10

Authors

Journals

citations
Cited by 516 publications
(368 citation statements)
references
References 14 publications
0
366
0
2
Order By: Relevance
“…One shortcoming of the probabilistic models is that the movements are represented at a single level of movement abstraction, and it is difficult to implement probabilistic modeling at multiple levels of movement abstraction. [128] Kinect v2 S Hand-crafted MA Saraee et al [156] Kinect v2 S Hand-crafted MA Taylor et al [45] Inertial sensor I Hand-crafted MC Zhang et al [48] Inertial sensor I Cross-correlation function MC Lin and Kulić [148] Inertial sensor S None MS Chen et al [183] Inertial sensor I Hand-crafted MC Zhang et al [138] Inertial sensor I None MA Houmanfar et al [53] Inertial sensor I Hand-crafted + LASSO MA Msayib et al [184] Inertial sensor S Hand-crafted MA Um et al [185] Inertial sensor I None DA Um et al [186] Inertial sensor I None MC Um et al [46] Inertial Table 4. Summary of approaches for evaluation of rehabilitation movements.…”
Section: B) Probability Density Functionsmentioning
confidence: 99%
“…One shortcoming of the probabilistic models is that the movements are represented at a single level of movement abstraction, and it is difficult to implement probabilistic modeling at multiple levels of movement abstraction. [128] Kinect v2 S Hand-crafted MA Saraee et al [156] Kinect v2 S Hand-crafted MA Taylor et al [45] Inertial sensor I Hand-crafted MC Zhang et al [48] Inertial sensor I Cross-correlation function MC Lin and Kulić [148] Inertial sensor S None MS Chen et al [183] Inertial sensor I Hand-crafted MC Zhang et al [138] Inertial sensor I None MA Houmanfar et al [53] Inertial sensor I Hand-crafted + LASSO MA Msayib et al [184] Inertial sensor S Hand-crafted MA Um et al [185] Inertial sensor I None DA Um et al [186] Inertial sensor I None MC Um et al [46] Inertial Table 4. Summary of approaches for evaluation of rehabilitation movements.…”
Section: B) Probability Density Functionsmentioning
confidence: 99%
“…For the training of BANet and of other architectures evaluated for comparison, we apply two augmentation techniques, both previously used in [15] [39]. The first technique is based on creating new instances by adding normalized Gaussian noise to the original data with 3 different standard deviations: 0.05, 0.1 and 0.15.…”
Section: Data Preparation and Experimental Settingsmentioning
confidence: 99%
“…Similar to image augmentation methods used to increase the amount of data available for training CNNs [16], Um et al [17] recently proposed several data augmentation methods for wearable sensors, and showed that augmentation significantly improved classification performance (for inertial data). We adopted three techniques from [17] (rotation, scaling, and jittering) to improve our model's invariance to factors such as IMU placement/orientation, shoe type, and gait type. For each training sample, we applied a random SO(3) rotation R (applied to a and ω for all data points in the sample), a random scaling factor, s ∈ [0.92, 1.02], to simulate faster or slower movement, and added zero-mean Gaussian noise n (σ = 0.075) to each channel.…”
Section: Trainingmentioning
confidence: 99%